Measures of star formation rates from infrared (Herschel) and UV (GALEX) emissions of galaxies in the HerMES fields - Buat, V.; Giovannoli, E.; Burgarella, D.; Altieri, B.; Amblard, A.; Arumugam, V.; Aussel, H.; Babbedge, T.; Blain, A.; Bock, J.; Boselli, A.; Castro-Rodríguez, N.; et al. (Wiley-Blackwell Publishing Ltd., 2010)
The reliability of infrared (IR) and ultraviolet (UV) emissions to measure star formation rates (SFRs) in galaxies is investigated for a large sample of galaxies observed with the Spectral and Photometric Imaging Receiver (SPIRE) and the Photodetector Array Camera and Spectrometer (PACS) instruments on Herschel as part of the Herschel Multi-Tiered Extragalactic Survey (HerMES) project. We build flux-limited 250-jj.m samples of sources at redshift z < 1, crossmatched with the Spitzer/MIPS and GALEX catalogues. About 60 per cent of the Herschel sources are detected in UV. The total IR luminosities, LIR, of the sources are estimated using a spectral energy distribution (SED) fitting code that fits to fluxes between 24 and 500 µm. Dust attenuation is discussed on the basis of commonly used diagnostics: the LIR/LUV ratio and the slope, ß, of the UV continuum. A mean dust attenuation AUV of ?3 mag is measured in the samples. LIR/LUV LIR. Galaxies with LIR > 1011 L? and 0.5 < z < 1 exhibit a mean dust attenuation AUV of about 0.7 mag lower than that found for their local counterparts, although with a large dispersion. Our galaxy samples span a large range of ß and LIR/LUV values which, for the most part, are distributed between the ranges defined by the relations found locally for starburst and normal star-forming galaxies. As a consequence the recipe commonly applied to local starbursts is found to overestimate the dust attenuation correction in our galaxy sample by a factor of ~2-3. The SFRs deduced from LIR are found to account for about 90 per cent of the total SFR; this percentage drops to 71 per cent for galaxies with SFR < 1 M? yr-1 (or LIR < 1010L?). For these faint objects, one needs to combine UV and IR emissions to obtain an accurate measure of the SFR. © 2010 The Authors. Journal compilation © 2010 RAS.